Chapter 5 The relative importance of selected factors affecting corporate trade credit policy - Koralun-Bereźnicka, Julia (Taylor & Francis, 2021)
Chapter 5 attempts to evaluate the relative importance of the country, industry and size effect in the corporate trade credit policies. This is done by analysing the multi-sectional clustering results based on various sets of variables. The different clustering results are compared to identify the prevailing factors affecting trade credit policies. First, the country effect was juxtaposed with the industry effect, and then with the firm size effect. Then, the relevance of the industry versus size effect was evaluated. The chapter also provides the similarity evaluation of clustering results, as well as the information on the contribution of trade credit variables to the classification results.